2012
DOI: 10.1063/1.4733321
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of Co2C and Co3C nanoparticles and their assemblies

Abstract: Nano-composite material consisting of Co 2 C and Co 3 C nanoparticles has recently been shown to exhibit unusually large coercivities and energy products. Experimental studies that can delineate the properties of individual phases have been undertaken and provide information on how the coercivities and the energy product change with the size and composition of the nanoparticles. The studies indicate that while both phases are magnetic, the Co 3 C has higher magnetization and coercivity compared to Co 2 C. Thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 42 publications
5
48
0
Order By: Relevance
“…Any residual solvent or unreacted salts were removed by washing 3 times with ethanol. Further details are described elsewhere [10,11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Any residual solvent or unreacted salts were removed by washing 3 times with ethanol. Further details are described elsewhere [10,11].…”
Section: Methodsmentioning
confidence: 99%
“…Recently a new class of hard magnetic materials based on nanocrystalline Co x C(x ¼2 or 3) have shown promise for these alternative energy applications. Cobalt carbide nanoparticles synthesized using a modified polyol process and described elsewhere [10][11][12]. These particles show a narrow size distribution, stability against oxidation, larger magnetocrystalline anisotropy, and larger coercivity.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have indicated that the transition metal based nanoparticles where the transition metal layers are separated by carbon (C) layers, exhibit large MAE. 31,32 We have also shown recently that small Co clusters diluted with C undergo significant enhancement in MAE. 33 Such enhancement of MAE in transition metal carbide (TMC) results due to the mixing of p states of C with d states of transition metal.…”
Section: -13mentioning
confidence: 92%
“…To investigate the unique evolution of the magnetic moment with a changing amount of carbon atoms incorporated into the metallic cobalt structure, Carpenter et al reported Co 2 C and Co 3 C nanocomposites both theoretically and experimentally. The authors showed that the addition of carbon atoms was critical to control the anisotropy of individual phases …”
Section: Structures Of Fe/co/ni Carbides and Nitridesmentioning
confidence: 99%